Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13690-020-00488-x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the proposed social health insurance among government-owned company employees in Northwest Ethiopia: implications for starting social health insurance implementation

Abstract: Background Ethiopia is currently planning to introduce Social Health Insurance (SHI) that will lead to universal health coverage and assist a country to achieve its health system’s objectives and to prevent the catastrophic health expenditure. But there is no evidence until now about the level of acceptance of the proposed SHI among government-owned companies’ employees. Therefore, this study was intended to assess the acceptance of SHI and associated factors among government-owned companies’ employees in nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
(44 reference statements)
6
15
3
Order By: Relevance
“…The total magnitude of WTP for SHI was 29.6%, with age, positive view of SHI, acute illness, level of education, and net family income being the factors that were significantly linked with the WTP for SHI. This was slightly similar to the findings of other studies conducted in Debere Berhan, Ethiopia (27.8%) ( 30 ) and Northwest Ethiopia (32%) ( 19 ). This result was discovered to be higher than that of studies conducted in Arba Minch, Southern Ethiopia (5.9%) ( 31 ) and at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia (17%) ( 32 ), but significantly lower than the findings of many other studies in Jimma, Southwest Ethiopia (90%) ( 13 ), Wolaita Sodo, South Ethiopia (74.4%) ( 15 ), Gondar, Northwest Ethiopia (62.0%) ( 11 ), Mekelle, Northern Ethiopia (85.3%) ( 23 ), Mujja, Ethiopia (37.6%) ( 33 ), Bahir Dar, Northwest Ethiopia (66.6%) ( 20 ), Mekelle, Northern Ethiopia (74.9%) ( 18 ), and public hospitals of Tigrai, Northern Ethiopia (35.5%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The total magnitude of WTP for SHI was 29.6%, with age, positive view of SHI, acute illness, level of education, and net family income being the factors that were significantly linked with the WTP for SHI. This was slightly similar to the findings of other studies conducted in Debere Berhan, Ethiopia (27.8%) ( 30 ) and Northwest Ethiopia (32%) ( 19 ). This result was discovered to be higher than that of studies conducted in Arba Minch, Southern Ethiopia (5.9%) ( 31 ) and at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia (17%) ( 32 ), but significantly lower than the findings of many other studies in Jimma, Southwest Ethiopia (90%) ( 13 ), Wolaita Sodo, South Ethiopia (74.4%) ( 15 ), Gondar, Northwest Ethiopia (62.0%) ( 11 ), Mekelle, Northern Ethiopia (85.3%) ( 23 ), Mujja, Ethiopia (37.6%) ( 33 ), Bahir Dar, Northwest Ethiopia (66.6%) ( 20 ), Mekelle, Northern Ethiopia (74.9%) ( 18 ), and public hospitals of Tigrai, Northern Ethiopia (35.5%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…The perceived quality of health-care services, on the other hand, was found to raise the WTP for SHI ( 18 ). It has also been reported that the ease with which past medical healthcare costs can be covered has a negative impact on the decision to pay for SHI ( 19 ). Alternatively, they may not have a history of financial difficulties in paying medical expenditures ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-rated perceived their health status was bad (73.9%) among Akaki Kality public school teachers in contrast to the previous study ndings, which was better among health professionals in government hospitals in Mekelle City for 87.5%[26] and among government-owned company employees in Northwest Ethiopia for 94.1% [27]; this might be due to the difference of target participant, time of study (COVID-19 outbreak era) and the institutions. The OOP payments for healthcare expenditures for teachers is 88.4%; which is lower compared to study on the willingness to pay for SHI among women from low-income HHs of Karachi, Pakistan (91%)[28] and a survey on long term health spending for individuals leaving in 11 emerging nations/countries with emerging economies paid 75.1-97.7% of their private healthcare expenditures was from direct OOP [16].…”
Section: Discussioncontrasting
confidence: 72%
“…Life insurance: the medical services given by the nurse within the working health institution. 21 Prospective views of the nursing profession: the better future view of the nurses toward the nursing profession. 2 Membership to the community: any members of health associations in the community such as the Ethiopian Nursing Association, to ease any collaborative work.…”
Section: Dependent Variablesmentioning
confidence: 99%